Pharmacological Potential of cis-jasmone in Adult Zebrafish (Danio rerio) - Bezerra, Francisca Magnólia Diógenes Holanda; Vieira-Neto, Antônio Eufrásio; Benevides, Samara Casemiro; Tavares, Kaio César Simiano; Ribeiro, Antonia Deyse de Castro; Santos, Sacha Aubrey Alves Rodrigues; Leite, Gerlânia de Oliveira; Alves Magalhães, Francisco Ernani; Campos, Adriana Rolim (Planta Medica, 2023)
This study evaluates the pharmacological potential of cis-jasmone (CJ) in adult zebrafish (Danio rerio; aZF). Initially, aZF (n = 6/group) were pretreated (20 µL; p. o.) with CJ (0.1 or 0.3 or 1.0 mg/mL) or vehicle (0.5% Tween 80). The animals were submitted to acute toxicity and locomotion tests, pentylenetetrazole-induced seizure, carrageenan-induced abdominal edema, and cinnamaldehyde-, capsaicin-, menthol-, glutamate-, and acid saline-induced orofacial nociception. The possible mechanisms of anticonvulsant, anxiolytic, and antinociceptive action were evaluated. The involvement of central afferent fibers sensitive to cinnamaldehyde and capsaicin and the effect of CJ on the relative gene expression of TRPA1 and TRPV1 in the brain of aZF were also analyzed, in addition to the study of molecular docking between CJ and TRPA1, TRPV1 channels, and GABAA receptors. CJ did not alter the locomotor behavior and showed pharmacological potential in all tested models with no toxicity. The anticonvulsant effect of CJ was prevented by flumazenil (GABAergic antagonist). The anxiolytic-like effect of CJ was prevented by flumazenil and serotonergic antagonists. The antinociceptive effect was prevented by TRPA1 and TRPV1 antagonists. Chemical ablation with capsaicin and cinnamaldehyde prevented the orofacial antinociceptive effect of CJ. Molecular docking studies indicate that CJ interacted with TRPA1, TRPV1, and GABAA receptors. CJ inhibited the relative gene expression of TRPA1 and TRPV1. CJ has pharmacological potential for the treatment of seizures, anxiety, inflammation, and acute orofacial nociception. These effects are obtained by modulating the GABAergic and serotonergic systems, as well as the TRPs and ASIC channels.
Keywords: cis-jasmone; seizure; anxiety; inflammation; acute orofacial nociception; GABAA and TRP receptors